Design Multiband Planar Printed Monopole Antenna With Minkowski And Lollipop Defected Parasitic Structure (DPS) For Wireless Communication System - Mohamad Hafize, Ramli; Mohamad Zainol Abidin, Abd Aziz; Mohd Azlishah, Othman; Abdul Halim, Dahalan (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
A multiband planar printed monopole antenna with Minkowski and Lollipop defected parasitic structure (DPS) for wireless communication system is proposed. The proposed antenna can create and work effectively to covers triband resonance frequencies at 2.4, 3.6 and 5.8 GHz within WLAN/WiMAX range in wireless communication system application. The Minkowski and Lollipop DPS has been place in front of and back of the multiband antenna that easily fed by using a 50 Ω microstrip line. The parametric study has been performed to analyze the best range of DPS from the proposed antenna. The simulated and measured impedance bandwidths for 10 dB return loss at first, second and third operating bands can be seen at (135 and 456) MHz, (380 and 272) MHz and (198 and 283) MHz respectively. The additional DPS helps to improve the return loss, bandwidth, gain, directivity. The simulation and measurement performance are well compared and discussed.